Influence of Andesitic Tuff Pozzolana on the Compressive Strength of a Mortar f ́c=300kg/cm2 - Medina Cabanillas, Edwar Sleyter; Carrion Rabanal, Katia Nataly (LACCEI, 2024)
This research analyzes the influence of andesitic tuff pozzolana as a substitute for cementitious material in percentages of 5%, 10% and 15% for a mortar made of f ́c 300 kg/cm2, which were cured at room temperature. The main objective is to determine the influence of the andesitic tuff pozzolana on the compressive strength of the f ́c 300kg/cm2 mortar. For this investigation, 32 specimens were made, which were tested in compression, at the ages of 7 and 15 days, determining that, at 7 days (M=125.31 kg/cm2, M5=130.54 kg/cm2, M10=127.91 kg/cm2, M15= 85.44 kg/cm2) and for 15 days (M=235.51 kg/cm2, M5=279.87 kg/cm2, M10=158.56 kg/cm2, M15= 127.54 kg/cm2). Replacing 5% of andesitic tuff pozzolana increases the resistance by 4.01% and 18.84% respectively at their ages of 7 and 15 days. Concluding that the andesitic tuff pozzolana optimally influences the mechanical property, resistance to compression of the mortar, obtaining as an optimal dosage the substitution of 5% giving noticeable favorable values ​​after 15 days, increasing its resistance to compression to 279.87 kg/cm2